Appraisals Analysis on the Argumentation Structure of Indonesian Undergraduate Students’ Research Articles - Reddy, Alfa Lisa Muslimah Febriyanti; Pradita, Intan (English Language Education, Universitas Internasional Batam, 2022)
This research aims to analyze the argument structure of undergraduate students’ research articles that focus on the introduction section. The data collection was conducted by analyzing the proceedings in the